Can energy drinks affect the surface quality of bioactive restorative materials? - Hazal Deniz Kose; Ilayda Giray; Hayal Boyacioglu; Lezize Sebnem Turkun (BMC, 2024)
Abstract Backgrounds This study aimed to compare the effects of different energy drinks on the surface roughness, weight loss, and color change of various bioactive restorative materials. Methods Charisma Diamond One, Activa™ BioActive Restorative, Activa™ Presto™ and Equia Forte HT Fil samples were prepared using plastic molds (8 × 2 mm) (n = 10/groups). After polishing, the samples were weighed, their colors were recorded using a spectrophotometer according to the CIEDE2000 system, and their surface roughness was measured using a profilometer. The samples were immersed in Powerade, Burn, Monster and distilled water for 7 days. After immersion, all the measurements were repeated. Statistical analyses were performed using the Wilcoxon signed-rank test and the Mann‒Whitney U test (p < 0.05). Results All energy drinks roughened the surface of Equia Forte HT Fil (p < 0.05). Powerade and Monster increased the Ra of all materials after 7 days (p < 0.05). Burns affected all materials except the Activa Bioactive (p < 0.05). Significant weight loss was observed in the Equia Forte group after immersion in all the energy drinks, whereas no weight loss was observed in the other groups. According to the color measurements, ΔE00 values were greater in the Burn and Monster groups, except for the Equia Forte HT Fil group (p < 0.05). Conclusion Energy drinks affected bioactive materials to varying degrees. The glass hybrid material was the most affected, and the bioactive restorative materials based on the resin matrix were the least.